2002
DOI: 10.1177/0145445502026002002
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Delayed Rewards, Tokens, and Stimulant Medication on Sportsmanlike Behavior with Adhd-Diagnosed Children

Abstract: Five children diagnosed with attention deficit/hyperactivity disorder participated in a summer program designed to evaluate behavioral and pharmacological treatments in a recreational setting. The effect of a contingency for increased sportsmanlike behavior, with and without the use of tokens, was examined during kickball games. The influence of stimulant medication was also examined for 3 of the children. A multiple-baseline, reversal design revealed that a delayed reward condition did not increase sportsmanl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 25 publications
0
23
0
1
Order By: Relevance
“…Ninth, the authors decided not to conduct or report an analysis of publication bias using techniques such as funnel plots because their interpretation is equivocal when based on a small number of studies, with difficulty in particular distinguishing between the effects of study heterogeneity and publication bias with sparse data. 36 In summary, although more evidence is required before behavioral interventions can be supported as a front-line treatment for core ADHD symptoms, the authors found evidence that they do have beneficial effects on parenting and parents' sense of empowerment and independently corroborated effects on conduct problems in children with ADHD. Initial evidence from proximal outcomes relating to academic achievement and social skills needs to be confirmed by probably blinded analyses and greater exploration is needed on the moderating impact of child age on intervention outcome.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 95%
See 2 more Smart Citations
“…Ninth, the authors decided not to conduct or report an analysis of publication bias using techniques such as funnel plots because their interpretation is equivocal when based on a small number of studies, with difficulty in particular distinguishing between the effects of study heterogeneity and publication bias with sparse data. 36 In summary, although more evidence is required before behavioral interventions can be supported as a front-line treatment for core ADHD symptoms, the authors found evidence that they do have beneficial effects on parenting and parents' sense of empowerment and independently corroborated effects on conduct problems in children with ADHD. Initial evidence from proximal outcomes relating to academic achievement and social skills needs to be confirmed by probably blinded analyses and greater exploration is needed on the moderating impact of child age on intervention outcome.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 95%
“…Following the recommendation of the Cochrane group, the search was limited to published trials to ensure a level of methodologic adequacy and rigor among included trials and to avoid the inevitable problems with securing access to a full set of unpublished trials and the bias that this would introduce. 36 Participants needed to be 3 to 18 years old and have an ADHD diagnosis (any subtype) or have met accepted cutoffs on validated ADHD rating scales. Trials involving only rare comorbid disorders (e.g., fragile X syndrome) were excluded.…”
Section: Accepted Manuscript Inclmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the initial task force review, however, there have been two large between-group Pelham, Burrows-MacLean et al, 2008a), five large crossover Fabiano 196 PELHAM AND FABIANO et al, 2004;Kolko et al, 1999;Pelham, BurrowsMacLean et al, 2008b;Pelham, Burrows-MacLean et al, 2005), and a number of well-controlled, singlesubject studies (e.g., Coles et al, 2005;Hupp et al, 2002;Reitman, Hupp, O'Callaghan, Gulley, & Northup, 2001) that report on the effect of BI for peer problems in recreational settings-typically STPs. In addition, the STP was a component of the MTA study.…”
Section: Behavioral Peer Interventionsmentioning
confidence: 99%
“…The late 1990s and early 2000s saw a surge in the publication of studies-clinical trials, large crossover studies, and single-subject designs-investigating the effectiveness of behavior modification for treating ADHD (e.g., Barkley et al, 2000;Chronis, Chacko, Fabiano, Wymbs, & Pelham, 2004;Hupp, Reitman, Northup, O'Callaghan, & LeBlanc, 2002;MTACG, 1999b;Pelham, Burrows-MacLean et al, 2005;SonugaBarke, Daley, Thompson, Laver-Bradbury, & Weeks, 2001). Perhaps the most well-known and widely cited study of treatments for ADHD is the Multimodal Treatment Study of ADHD (MTA; Conners et al, 2001;Jensen, 2001;MTACG, 1999aMTACG, , 1999bSwanson et al, 2001;Wells et al, 2000).…”
mentioning
confidence: 99%